A Comparative Analysis of Michaelis-Menten, Hill, and Allosteric Models in Drug Metabolism - Ziyad K. Radeef (Iraqi Journal of Industrial Research, 2025)
Background: Enzyme Kinetics it is a fundamental part of metabolic biochemistry because it helps to explore the mechanism of action and interaction of all substrates under the influence as well as environmental factors. Aim: The present study intends to compare the kinetic models that have been employed to assess their efficacy in pharmaceutical kinetics and drug-trans metabolizing enzymes and efficiency. Study Design: Methodology and Experimental Design: The data were collected for separate enzymes (CYP3A4, CYP2D6 and UDP-glucuronosyltransferase) at different substrate concentrations and fit comparison analysis based on the accuracy of fit, residuals, and Akaike Information Criterion (AIC) scores and R-squared (R²). Enzymes at high concentrations that exhibit cooperative behaviour or synergistic regulation may require advanced kinetic models such as the Hill model and the allosteric models, with a focus on the analysis at optimal conditions and Akaike Information Criterion (AIC) scores. Results: The Michaelis-Menten model was effective for non-cooperative systems; however, for enzymes demonstrating cooperative binding, like CYP2D6, the Hill model showed improved predictive capabilities. The allosteric model consistently outperformed the Michaelis-Menten and Hill models in capturing the observed velocities across a variety of enzyme-substrate pairs, particularly for enzymes exhibiting allosteric behavior. Conclusion: The study showed that Michaelis-Menten model effectively describes basic enzyme kinetics, particularly at low substrate concentrations, where simple saturation kinetics apply. The Hill model incorporates cooperatively, making it particularly useful for enzymes like CYP3A4 that exhibit sigmoidal kinetics. The Allosteric model is the most versatile, as it accommodates cooperative and regulatory effects over a broad range of substrate concentrations.